GAMBARAN PENGETAHUAN DAN SIKAP PERAWAT DALAM PELAKSANAAN DISCHARGE PLANNING PADA PASIEN DIABETES MELLITUS TYPE II - Okatiranti, Okatiranti (LPPM BSI Bandung, 2015)
Abstrack - Implementation of discharge planning in adult patients would improve patient knowledge, effective care at home, thereby reducing repeated visits to the hospital, and reduced maintenance costs (Slaganfall, 1992). Nurses play a role as an educator in the implementation of discharge planning. Descriptive research method was to see the picture of the knowledge and attitudes of nurses in the implementation of discharge planning in patients with Diabetes Mellitus, with a population of nurses was working in intern wards, have used total sampling technique. The data was collected using a questionnaire. Then interpreted using tabulation and calculation prosentase. Result, knowledge and attitude studies showed the implementation of discharge planning nurses in public hospitals and private hospitals in the Bandung. Most nurses have less knowledge (51.35%) and nearly half (43.2%) have sufficient knowledge and a fraction having a good knowledge (5.4%). As for the components of the overall attitude more than half (54%) unfavorable, and nearly half (46%) of nurses to support (favorable) the implementation of discharge planning.Keywords: discharge planning, nursing, knowledge, attitudes Abstrak - Pemberian discharge planning pada pasien dewasa akan meningkatkan pengetahuan pasien, efektifnya perawatan di rumah sehingga mengurangi kunjungan ulang ke rumah sakit, dan mengurangi biaya perawatan (Slaganfall, 1992). Perawat memegang peranan sebagai pendidik dalam pelaksanaan discharge planning. Metode penelitian deskriptif untuk melihat gambaran pengetahuan dan sikap perawat dalam pelaksanaan discharge planning pada pasien Diabetes Mellitus, dengan populasi perawat yang bekerja di ruang penyakit dalam, Teknik sampling dengan total sampling . Data dikumpulkan dengan menggunakan kuisioner atau angket. Kemudian diinterpretasikan dengan menggunakan tabulasi dan perhitungan prosentase.Hasil penelitian menunjukkan pengetahuan dan sikap perawat pelaksanaan discharge planning di rumah sakit pemerintah dan rumah sakit swasta di kota Bandung. Sebagian besar perawat mempunyai pengetahuan yang kurang (51,35 %) dan hampir setengahnya (43,2%) mempunyai pengetahuan cukup dan sebagian kecil mempunyai pengetahuan yang baik (5,4%). Sedangkan untuk komponen sikap secara keseluruhan lebih dari setengah (54 %) tidak mendukung dan hampir setengahnya (46%) perawat mendukung pelaksanaan discharge planning. Kata kunci : discharge planning, perawat, pengetahuan, sikap